THE EFFECT OF INTELLECTUAL CAPITAL DISCLOSURE ON FINANCIAL PERFORMANCE IN INDONESIAN BANKING COMPANIES - Tang, Sukiantono (Media Ekonomi, 2023)
Financial Performance is the analysis conducted to determine the extent to which a company has correctly and adequately implemented the rules of financial performance. The purpose of this study is to discover and obtain empirical evidence on the impact of exposure to intellectual capital on financial performance. The survey was conducted from 2018 to 2022 for banking companies listed on the Indonesian Stock Exchange. The results for the selected samples are 225 data for ROA, and 222 data for ROE. The data analysis technique used is linear regression analysis. The result is an outflow of intellectual capital financial performance using ROA and ROE.